Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1203/00006450-199512000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal Pulmonary Ventilation versus Conventional Mechanical Ventilation in a Rabbit Model of Surfactant Deficiency

Abstract: Intratracheal pulmonary ventilation (ITPV) enhances the clearance of CO, from dead space and lungs by a bias flow of gas administered in the distal trachea. ITPV flow is continuously administered through a separate catheter placed within an endotracheal tube (ETT). After exiting from catheter's tip in the distal trachea, the flow of gas is redirected outward away from the lungs. We hypothesized that, compared with conventional mechanical ventilation (CMV), ITPV may increase minute CO, clearance (vco,), reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 8 publications
(16 reference statements)
2
11
0
Order By: Relevance
“…This was confirmed by our group when we demonstrated, that LPA not only promotes epithelial wound healing in vitro by a TGF-β-independent pathway, but also ameliorates experimental colitis in an experimental model of colitis in rats [61] . Interestingly, also lysophosphatidylethanolamine and lisofylline, which decreases lipid peroxidation, significantly Short chain fatty acids Stimulate intestinal epithelial migration [63,76] Glutamine Stimulates intestinal epithelial proliferation and migration [76,77] reduced the degree of inflammation and necrosis in an experimental colitis model [69] , demonstrating that the administration of anti-inflammatory lysophospholipids and suppression of pro-inflammatory lipid metabolites by lisofylline may provide new approaches to ameliorate intestinal inflammation. This beneficial effect could also be demonstrated in other diseases since lisofylline and its analogs reversed autoimmune diabetes in a non-obese diabetic (NOD) mouse model and thus might act as a potential treatment for Type 1 diabetes [70,71] .…”
Section: Modulation Of Intestinal Epithelial Wound Healing By Non-pepmentioning
confidence: 99%
“…This was confirmed by our group when we demonstrated, that LPA not only promotes epithelial wound healing in vitro by a TGF-β-independent pathway, but also ameliorates experimental colitis in an experimental model of colitis in rats [61] . Interestingly, also lysophosphatidylethanolamine and lisofylline, which decreases lipid peroxidation, significantly Short chain fatty acids Stimulate intestinal epithelial migration [63,76] Glutamine Stimulates intestinal epithelial proliferation and migration [76,77] reduced the degree of inflammation and necrosis in an experimental colitis model [69] , demonstrating that the administration of anti-inflammatory lysophospholipids and suppression of pro-inflammatory lipid metabolites by lisofylline may provide new approaches to ameliorate intestinal inflammation. This beneficial effect could also be demonstrated in other diseases since lisofylline and its analogs reversed autoimmune diabetes in a non-obese diabetic (NOD) mouse model and thus might act as a potential treatment for Type 1 diabetes [70,71] .…”
Section: Modulation Of Intestinal Epithelial Wound Healing By Non-pepmentioning
confidence: 99%
“…Makhoul et al reported that TGI could minimize lung barotrauma associated with mechanical ventilation in a rabbit model of surfactant deficience [12]. Miro et al demonstrated that TGI increases the efficiency of CO 2 elimination during constant and decreased minute ventilation conditions without any evidence of hyperinflation or hemodynamic instability in a dog model of asthma [13].…”
Section: Discussionmentioning
confidence: 99%
“…Severe lung injury was then created in all animals by repeat endotracheal saline lavage (12 mL/kg each lavage), as previously described [7,8]. The degree of lung injury was deemed satisfactory when the arterial Po 2 and Pco 2 were stable (at V120 or z55 mm Hg, respectively), on conventional ventilation, with the following parameters: Fio 2 of 100%; respiratory rate (RR) of 25 bpm; peak inspiratory pressure (PIP) of 25 cm H 2 O; and positive end-expiratory pressure (PEEP) of 5 cm H 2 O.…”
Section: Methodsmentioning
confidence: 99%